Sistem Pengamanan Anonym dengan Menggunakan Algoritma Kriptografi ElGamal - Anggreni, Ni Komang Ayu Sri; Linawati, Linawati; Sastra, Nyoman Putra (Majalah Ilmiah Teknologi Elektro, 2019)
Reporting on act of domestic violence to Integrated Services Center for Woman and Children (Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A)) Kota  Denpasar city is kind of sensitive and vulnerable data to tapping. As a result, security guarantee for the reporter  is needed to protect their identity. Security guarantee with anonym reporting system, which uses EIGamal cryptographic algorithm for encryption process and description process.  EIGamal cryptographic algorithm is one of asymmetric cryptography which consist of  3 processes, that are process  of generate key, encryption  process and description process  On this security system identity of the reporter will be protected through  process of authentication, authorization, and encryption. In this study the researcher uses Android platform and EIGamal cryptographic algorithm for encryption and description, Firebase Auth  for authentication, Firebase Rules for authorization and Avalanche Effect  for knowing the quality of cryptographic algorithm. The result of the trials  which used 10 different ciphet texts of avalanche effect is 58,2%. That result can be categorized as good because a good result of avalanche effect.